Book Review Peace, Reform and Liberation: A History of Liberal Politics in Britain 1679-2011. Edited by Robert Ingham and Duncan Brack. London: Biteback Publishing. 2011. pp. xviii+414 £30. ISBN 978-184954-043-8. Issue 1 (2012) - Mackley, Simon
No abstract available